The Role of Temporary Waqf in Improving the Social Welfare of the Muslim Community - ., Johari; ., Wahidin; ., Maghfirah; ., Zulkifli; ., Mawardi; Maulidizen, Ahmad (Journal of Ecohumanism, 2024)
Temporary waqf, as an innovative form of waqf, offers a level of flexibility that permanent waqf lacks. By allowing fund allocation for a set period, temporary waqf holds significant potential for improving social welfare of the Muslim Community. It enables the use of funds to respond quickly to urgent and varied needs, such as infrastructure development and public facilities. This study seeks to evaluate the effectiveness of temporary waqf in enhancing social welfare of the Muslim Community, focusing on fund allocation flexibility, investment efficiency, and positive economic impacts. The research adopts a library research approach, collecting and analyzing relevant literature on temporary waqf. Data are sourced from academic publications, regulatory documents, and waqf management-related reports. The analysis examines how temporary waqf affects the execution of social and economic projects and its overall influence on the community. Results indicate that temporary waqf allows for more adaptable and responsive fund allocation, accelerating the implementation of both social and economic programs. Temporary waqf funds can be invested in productive projects that generate immediate benefits, such as building infrastructure and healthcare facilities. These projects contribute to improving the quality of life, stimulating local economic growth, and creating employment opportunities. The study suggests raising public awareness about temporary waqf, formulating supportive policies, and promoting collaboration with the private sector and financial institutions. By implementing these recommendations, temporary waqf can further maximize its impact, enhance fund management efficiency, and contribute to sustainable development across Muslim Community.